The Saigon sisters privileged women in the resistance - Norland, Patricia (NIU Southeast Asian series., 2021)
This text offers the narratives of a group of privileged women who were immersed in a French lycée and later rebelled and fought for independence, starting with France's occupation of Vietnam and continuing through US involvement and life after war ends in 1975. Tracing the lives of nine women, the book reveals these women's stories as they forsook safety and comfort to struggle for independence, and describes how they adapted to life in the jungle, whether facing bombing raids, malaria, deadly snakes, or other trials.